2022
DOI: 10.3389/fimmu.2022.864314
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Regions of Pathogenic Th17 Related Chromatin Loci Are Sequentially Accessible During Pathogenicity of Th17

Abstract: Pathogenic Th17, featured by their production of pro-inflammatory cytokines, are considered as a key player in most autoimmune diseases. The transcriptome of them is obviously distinct from that of conventional regulatory Th17. However, chromatin accessibility of the two Th17 groups have not been comprehensively compared yet. Here, we found that their chromatin-accessible regions(ChARs) significantly correlated with the expression of related genes, indicating that they might engage in the regulation of these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Therefore, we also investigated the genomic distribution of these ILC and Th concordant and non-concordant OCRs. Consistent with the previous studies (39)(40)(41), ILC concordant OCRs demonstrated a preferential distribution within 1 kilobase pair (kb) around TSSs compared with the Th concordant OCRs (Figure 3H). However, the distribution of ILC non-concordant OCRs did not show such a tendency (Supplementary Figure 4F).…”
Section: Expression-concordant Opening Chromatin Regions Associated W...supporting
confidence: 91%
“…Therefore, we also investigated the genomic distribution of these ILC and Th concordant and non-concordant OCRs. Consistent with the previous studies (39)(40)(41), ILC concordant OCRs demonstrated a preferential distribution within 1 kilobase pair (kb) around TSSs compared with the Th concordant OCRs (Figure 3H). However, the distribution of ILC non-concordant OCRs did not show such a tendency (Supplementary Figure 4F).…”
Section: Expression-concordant Opening Chromatin Regions Associated W...supporting
confidence: 91%
“…Among them, the concordant ChARs were further defined, based on two criteria: (1) ChARs related to the upregulated genes showed the highest accessibility or likewise ChARs related to the downregulated genes showed the lowest accessibility and (2) accessibility of these ChARs displayed at least 1.25-fold changes between the additional IL-21-stimulated trNK and the unstimulated or PMA/ionomycin-stimulated trNK ( Figures 7 B and S7 A). 40 Accordingly, we identified 294 concordant ChARs for the additional IL-21 stimulation-upregulated genes and 433 concordant ChARs for the additional IL-21 stimulation-downregulated genes ( Figure 7 C). Although their related genes did not account for a large proportion of the total upregulated or downregulated genes by the additional IL-21 stimulation, their enriched features recapitulated the additional IL-21 stimulation-induced changes in trNK, suggesting that the regulation of these genes might be still important ( Figure 7 D and 7E).…”
Section: Resultsmentioning
confidence: 85%
“…The pathogenetic role of Th17-cells in immune-mediated glomerular diseases and ischemia- reperfusion injury has been demonstrated recently by us and others [ 15 , 22 , 46 49 ]. The exact molecular mechanisms how Th17-cells are regulated once infiltrating into the kidney and how Th17-cells induce kidney injury by attacking endogenous renal glomerular, tubular epithelial and vascular endothelial cells or kidney fibroblasts remains to be defined [ 50 52 ].…”
Section: Discussionmentioning
confidence: 99%